Mortality from respiratory infections and chronic non-communicable diseases before the COVID-19 pandemic in Cali, Colombia. (Colombia Medica, 2020)
Introduction: The COVID-19 disease pandemic is a health emergency. Older people and those with chronic noncommunicable diseases are more likely to develop serious illnesses, equire ventilatory support, and die from complications.Objective: To establish deaths from respiratory infections and some chronic non-communicable diseases that occurred in Cali, before the SARS-CoV-2 disease pandemic.Methods: During the 2003-2019 period, 207,261 deaths were registered according to the general mortality database of the Municipal Secretary of Health of Cali. Deaths were coded with the International Classification of Diseases and causes of death were grouped according to WHO guidelines. Rates were standardized by age and are expressed per 100,000 people-year.Results: A direct relationship was observed between aging and mortality from respiratory infections and chronic non-communicable diseases. Age-specific mortality rates were highest in those older than 80 years for all diseases evaluated. Seasonal variation was evident in respiratory diseases in the elderly.Comments: Estimates of mortality rates from respiratory infections and chronic non-communicable diseases in Cali provide the baseline that will serve as a comparison to estimate the excess mortality caused by the COVID-19 pandemic. Health authorities and decision makers should be guided by reliable estimates of mortality and of the proportion of infected people who die from SARS-CoV-2 virus infection.